2010
DOI: 10.1126/science.1181421
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Short RNAs Reveals Widespread Promoter-Proximal Stalling and Arrest of Pol II in Drosophila

Abstract: Emerging evidence indicates that gene expression in higher organisms is regulated by RNA polymerase II stalling during early transcription elongation. To probe the mechanisms responsible for this regulation, we developed methods to isolate and characterize short RNAs derived from stalled RNA polymerase II in Drosophila cells. Significant levels of these short RNAs were generated from over one third of all genes, indicating that promoter-proximal stalling is a general feature of early polymerase elongation. Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
555
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(592 citation statements)
references
References 28 publications
(61 reference statements)
31
555
3
3
Order By: Relevance
“…Polyclonal rat aWOC (IF: 1/500) and rabbit aROW (WB: 1/10,000, ChIP/IP: 1 ml) antibodies were raised against recombinant proteins aa230-626 and aa588-956, respectively. Other antibodies used are described in the indicated references: rat aHP1c (WB: 1/10,000, IF: 1/500, ChIP/IP: 1 ml), aHP1b (WB: 1/ 10,000, ChIP/IP: 1 ml) and aROW (WB: 1/10,000, IF: 1/400, ChIP/IP: 1 ml) 18 , rabbit aWOC (WB: 1/10,000, ChIP/IP: 1 ml) 62 , rabbit and rat aDDP1 (ChIP/IP: 1 ml) 63 , rabbit adDsk2 (WB: 1/12,000, IF: 1/1,000, ChIP/IP: 1 ml) 16 , mouse ap54 (WB: 1/50) 64 , rabbit aNELF-E (WB: 1/500, ChIP/IP: 3 ml) 65 and rabbit aRPB3 (WB: 1/1,500, ChIP: 15 ml) 26 . Commercially available antibodies used were as follows: rabbit aH3K4me3 (Abcam, ab8580, ChIP: 1 ml), rabbit aIIoser5 (Abcam, ab5131, ChIP: 3 ml), rabbit aBre1 (NOVUS, 40280002, WB: 1/1,000, ChIP: 2 ml) and aRad6 (SANTA CRUZ, sc-30078, WB: 1/500, ChIP: 2 ml), mouse aGST (glutathione S-transferase; Novagen, 71097-3, WB: 1/10,000), mouse aGFP (Roche, 1814460, IF: 1/50), mouse aH2Bub1 (Millipore, 05-1312, WB: 1/4,000, ChIP/IP: 1 ml), mouse aTubulin (Millipore, MAB3408, WB: 1/2,000), rabbit aActin (Sigma, A2066, WB: 1/10,000), mouse aV5 (Invitrogen, 460705, WB: 1/5,000), mouse aUbiquitin (SANTA CRUZ, sc-8017, WB: 1/500), rabbit aPanAc (Abcam, Ab193-100, ChIP: 1 ml) and rabbit aH4Ac (Millipore, no.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyclonal rat aWOC (IF: 1/500) and rabbit aROW (WB: 1/10,000, ChIP/IP: 1 ml) antibodies were raised against recombinant proteins aa230-626 and aa588-956, respectively. Other antibodies used are described in the indicated references: rat aHP1c (WB: 1/10,000, IF: 1/500, ChIP/IP: 1 ml), aHP1b (WB: 1/ 10,000, ChIP/IP: 1 ml) and aROW (WB: 1/10,000, IF: 1/400, ChIP/IP: 1 ml) 18 , rabbit aWOC (WB: 1/10,000, ChIP/IP: 1 ml) 62 , rabbit and rat aDDP1 (ChIP/IP: 1 ml) 63 , rabbit adDsk2 (WB: 1/12,000, IF: 1/1,000, ChIP/IP: 1 ml) 16 , mouse ap54 (WB: 1/50) 64 , rabbit aNELF-E (WB: 1/500, ChIP/IP: 3 ml) 65 and rabbit aRPB3 (WB: 1/1,500, ChIP: 15 ml) 26 . Commercially available antibodies used were as follows: rabbit aH3K4me3 (Abcam, ab8580, ChIP: 1 ml), rabbit aIIoser5 (Abcam, ab5131, ChIP: 3 ml), rabbit aBre1 (NOVUS, 40280002, WB: 1/1,000, ChIP: 2 ml) and aRad6 (SANTA CRUZ, sc-30078, WB: 1/500, ChIP: 2 ml), mouse aGST (glutathione S-transferase; Novagen, 71097-3, WB: 1/10,000), mouse aGFP (Roche, 1814460, IF: 1/50), mouse aH2Bub1 (Millipore, 05-1312, WB: 1/4,000, ChIP/IP: 1 ml), mouse aTubulin (Millipore, MAB3408, WB: 1/2,000), rabbit aActin (Sigma, A2066, WB: 1/10,000), mouse aV5 (Invitrogen, 460705, WB: 1/5,000), mouse aUbiquitin (SANTA CRUZ, sc-8017, WB: 1/500), rabbit aPanAc (Abcam, Ab193-100, ChIP: 1 ml) and rabbit aH4Ac (Millipore, no.…”
Section: Methodsmentioning
confidence: 99%
“…shortRNA-Seq data were downloaded from NCBI GEO (GSE18643) 26 . shortRNA sites were defined as those with a score above the third quartile and annotated for overlapping genes as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ser7 of the CTD can also be phosphorylated, which has been linked to small nuclear RNAs (snRNA) transcription and recruitment of the integrator complex [9][10][11][12][13] . Whereas some genes, for example, those on CpG islands, can directly proceed to the elongation state by recruiting P-TEFb to RNAPII 14 , genomewide studies suggest that the majority of genes in higher eukaryotes are under the control of promoter-proximal pausing [15][16][17] .…”
mentioning
confidence: 99%
“…The kinase activity of P-TEFb Drosophila cells revealed that loss of NELF-mediated pausing reduced RNA Pol II promoter occupancy at most, but not all, promoters, 2 globally implicating NELF in inhibition of early elongation. The high sensitivity of the global runon-sequencing (GRO-seq) technique, 51 allowed the determination that even active genes undergo transient pausing of RNA Pol II, 47,52 suggesting that NELF-mediated pausing may be a general feature of the transcription mechanism. Furthermore, these studies suggest that the efficiency of pause release, rather than the establishment of pausing, plays a major role in determining gene expression levels.…”
Section: Sp3 Regulates the Balance Of Kinase And Phosphatase Activitimentioning
confidence: 99%